Organização e dinâmica da mobilização e participação política: os grêmios estudantis das escolas públicas e privadas de Santa Maria - RS - Soares, José Galdino Barreto (2019)
The present study presents results of a work about the dynamics of the organization of the student councils of Santa Maria - RS. This study seeks to contribute with empirical analysis about the structure, organization, type of predominant activity, mobilization and student participation in the researched student groups. The main objective of this study is to verify how these student entities act in Santa Maria schools, trying to point out and explain what is the predominant type of political activity carried out by their leaders and if these actions are being able to mobilize the participation of high school students in the spaces of decision making. decisions. This work was carried out between 2017 and 2018 in seven schools of Santa Maria - RS, five of the state school system and two of the private school system. In terms of methodological procedures, a block-based questionnaire with closed and open questions was applied to the student guiding students of the student councils and the minutes of these entities were analyzed, thus constituting a non-probabilistic quantitative and qualitative sample. In theoretical terms, this work operates taking into account one of the results of the research carried out by JA Guilhon Albuquerque (1977), which is as follows: in associations that carry out cultural, recreational and welfare political activities, the participation of students tends to be weaker. and stronger in party associations. One of the purposes of this study is to verify, empirically, if this research result found by Albuquerque (1977) is confirmed in the case of the student groups of Santa Maria. Analysis of the data indicates that the seven student councils are unable to mobilize non-member students to the point where they participate in decision-making that is usually made by the governing group alone. Thus, the involvement of students who are not members of the student council leadership is mostly restricted to formal decision-making structures, that is, the choice of student council direction through electoral processes (by voting) and participation in events. when these are performed.